Impact of Asymmetric Carbon Information on Supply Chain Decisions under Low-Carbon Policies - Lei Yang; Jingna Ji; Chenshi Zheng (Discrete Dynamics in Nature and Society)
Through the establishment of the leading manufacturer Stackelberg game model under asymmetric carbon information, this paper investigates the misreporting behaviors of the supply chain members and their influences on supply chain performance. Based on “Benchmarking” allocation mechanism, three policies are considered: carbon emission trading, carbon tax, and a new policy which combined carbon quota and carbon tax mechanism. The results show that, in the three models, the leader in the supply chain, even if he has advantages of carbon information, will not lie about his information. That is because the manufacturer’s misreporting behavior has no effect on supply chain members’ performance. But the retailer will lie about the information when he has carbon information advantage. The high-carbon-emission retailers under the carbon trading policy, all the retailers under the carbon tax policy, and the high-carbon-emission retailers under combined quotas and tax policy would like to understate their carbon emissions. Coordination of revenue sharing contract is studied in supply chain to induce the retailer to declare his real carbon information. Optimal contractual parameters are deduced in the three models, under which the profit of the supply chain can be maximized.